Prospects and Expediency of Implementing the Use of Vertical Preparation of Hard Tissues of Teeth in Orthopedic Dentistry (Literature Review) - Doroshenko О. М.; Veklenko Р. Г.; Ostrovskyi Р. В.; Ostrovskyi Я. В. (Actual Dentistry, 2024)
Introduction. In 2013, modified vertical preparation, also known as biologically oriented preparation technique (BOPT), was proposed to benefit both short- and long-term soft tissue stability. BOPT is a procedure to eliminate the anatomical appearance of the crown at the cemento-enamel ju ction (CEJ) and create a new connection with a fixed prosthesis during prosthesis placement and is a consolidated concept of pericoronal soft tissue modeling and preservation. The purpose of BOPT is to stabilize the gingival tissue in the medium and long term and to preserve the biological width through controlled penetration into the sulcus during tooth preparation. This avoids the complications associated with conventional horizontal subgingival preparation, where restorations are placed below the gingival margin, which is associated with periodontal inflammation and possible gingival displacement Goal. Based on the analysis of literary sources, the prospects and expediency of implementing the vertical preparation of hard tooth tissues in orthopedic dentistry are determined. Materials and methods. Information search and analysis of scientific sources was done using scientometric databases Web of Science, PubMed, and Google Scholar over the last 10 years. Conclusion. The analysis of literature sources allowed us to conclude that although the BOPT technique has shown significant advantages in stabilizing soft tissues and improving the aesthetics of prostheses, further research is needed to better understand its long-term results and possible complications. Studies comparing BOPT with other methods regarding periodontal effects, tissue adaptation, and predicting outcomes in patients with different gingival types are particularly important. Additional clinical trials will help improve the technique and establish clear protocols for its use in various clinical cases.